Application of Genetic Algorithm with Roulette Wheel Selection Method for International Certification Scheduling Optimization at ITCC ITPLN - Jatnika, Hendra; Rakhmadi Irfansyah Putra; Muhammad Zaid Al-Khair; Arfani Lovina Br. Stendel; Mohamad Tanwirul Akbar (Politeknik Piksi Ganesha Indonesia, 2022)
Information Technology Certification Center (ITCC) is a division within the PLN Institute of Technology, authorized to conduct international training and certification. During the scheduling process, it was identified that the current schedule creation was not optimal. Therefore, an optimization algorithm was required to address the scheduling issues. The chosen algorithm was the genetic algorithm with roulette wheel selection, applied to a prototype, followed by black-box testing of the prototype and ANOVA for the algorithm’s. The findings of the research suggest that the genetic algorithm with roulette wheel selection can generate an optimal schedule for international certification activities while adhering to established rules